2003
DOI: 10.1021/jf034834n
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Static Headspace, Headspace Solid Phase Microextraction, Headspace Sorptive Extraction, and Direct Thermal Desorption Techniques on Chemical Composition of French Olive Oils

Abstract: Static headspace (SHS), headspace solid phase microextraction (HS-SPME), headspace sorptive extraction (HSSE), and direct thermal desorption (DTD) were applied to the analysis of four French virgin olive oils from Corsica. More than 60 compounds were isolated and characterized by GC-RI and GC-MS. SHS was not suited to the characterization of olive oil volatile compounds because of low sensitivity. The SPME and HSSE techniques were successfully applied to olive oil headspace analysis. Both methods allow the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(107 citation statements)
references
References 27 publications
6
100
0
1
Order By: Relevance
“…The first aim of this study was to identify whether the volatile organic compounds can be used to evaluate the behaviour of fruit fly and stable isotope 13 C 6 -glucose on different stages of volatile compounds of Medfly. Previous researches employed analytical techniques based on thermal desorption, solvent extraction and headspace, which were explained the differences in medfly volatile profiles [20]. This study showed that the fruit fly emitted different VOCs when treated by a stable isotope, especially with adult treatment [21].…”
Section: Gc-fid Compounds and Analysementioning
confidence: 79%
See 1 more Smart Citation
“…The first aim of this study was to identify whether the volatile organic compounds can be used to evaluate the behaviour of fruit fly and stable isotope 13 C 6 -glucose on different stages of volatile compounds of Medfly. Previous researches employed analytical techniques based on thermal desorption, solvent extraction and headspace, which were explained the differences in medfly volatile profiles [20]. This study showed that the fruit fly emitted different VOCs when treated by a stable isotope, especially with adult treatment [21].…”
Section: Gc-fid Compounds and Analysementioning
confidence: 79%
“…To identify the main peaks, the value of each compound with respect to the total integrated peaks was calculated to compare the emission between compounds in the same treatment. The main chemicals include ethyl acetate and ethyl (E)-3-hexenoate which recorded by Cavalli et al [20]. …”
Section: Identification Of Volatile Constituents From Pupae Stagementioning
confidence: 99%
“…SPME has been proposed as a method for analysis of potential markers for oxidation status (nonanal proposed as indicator) (Vichi et al 2003), or quality-freshness markers of olive oil ((E)-hex-2-enal, C6 alcohols and C5 ketones) (Cavalli et al 2004), although in many papers describing its use in flavor analysis, it is based mainly on area count comparison, not a quantitative method (Jeleń et al 2012). A comparative study was performed in which static headspace was compared to headspace solid-phase microextraction, headspace sorptive extraction and direct thermal desorption (Cavalli et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Employment of high temperature for the isolation of volatile compounds using distillation methods may result in their degradation, or in formation of artifacts. Headspace techniques such as static or dynamic headspace (SHS or DHS, respectively), headspace sorptive extraction (HSSE), solid-phase microextraction (SPME), and direct thermal desorption (DTD) are robust methods which do not require the use of a solvent or circumstances which impede obtaining a pure volatile compound extract of the analyzed sample (Bylaite and Meyer 2006;Cavalli et al 2003). Each of these methods enables the isolation of volatile compounds usually without artifacts' formation.…”
Section: Introductionmentioning
confidence: 99%
“…These previous works employed analytical techniques based on headspace, thermal desorption and solvent extraction, what could explain the differences in medfly volatile profiles. Volatile collection techniques have been compared by some authors (Cavalli et al, 2003;González-Mas et al, 2009), demonstrating that the technique employed has influence on the kind of compounds which were collected and identified.…”
Section: Viii3 Results and Discussionmentioning
confidence: 99%